Bentuk-Bentuk Pelanggaran Profesi Notaris di Kabupaten Sidoarjo - Diana Ika Lestari; Miftakhul Huda (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to find out what are the forms of violations of the notary profession in Sidoarjo Regency. The method used is sociological juridical where this approach is to identify and carry out the conception of law as a real and functional social institution in a real life. The data was carried out by direct interviews with the Chairperson of the Notary Regional Supervisory Council of Sidoarjo Regency, as well as taking an inventory of the types of violations that occurred according to their categories. And other data is also done by collecting primary data in the form of interview and secondary data in the form of law and legal journals related to the topic being studied. This violation of the notary profession can occur due to several factors, especially the notary's disobedience in carrying out his duties, not guided by the code of ethics and also the law. From this research, it can be concluded that in Sidoarjo Regency there are several forms of notary professional violations, both those that violate the code of ethics and those that violate the law, such as installing a nameplate that is not in accordance with existing regulations to fraud and/or embezzlement of tax deposits.